Influence of Applied Potential on The Structural and Optical Properties of Cu2O Thin Films Grown by Electrochemical Deposition - Akhiruddin Maddu (Jurnal Sains Materi Indonesia, 2022)
Cu2O thin films have been deposited on indium-tin-oxide (ITO) coated glass substrate by electrochemical method or electrodeposition. The effect of deposition potential on the microstructure and optical properties of Cu2O thin films was studied. Electrodeposition for two Cu2O thin films was carried out at –0.5V and –0.6V relative to the standard calomel electrode (SCE) as a reference electrode. Cu2O thin films were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), and UV-Visible spectroscopy. The diffraction pattern indicated the cubic structure of the Cu2O crystal has been well grown. The lattice parameters of Cu2O films slightly increased as the potential of electrodeposition increased. The crystallite size of Cu2O films significantly increased as the applied potential increased. Cu2O thin films showed a smooth and flat surface morphology based on SEM images. The optical transmittance of the Cu2O thin films drastically decreased as the applied potential increased due to the film thickness increasing. The bandgap energy of Cu2O films based on the Tauc plot increased as the applied potential increased, that is 2.0 eV for the film deposited at -0.5V and 2.13 eV deposited at -0.6V.